Knowledge of Sugar Content of Sports Drinks is Not Associated with Sports Drink Consumption. Issue 2 (November 2015) - Zytnick, Deena; Park, Sohyun; Onufrak, Stephen J.; Kingsley, Beverly S.; Sherry, Bettylou
Purpose: To examine U.S. adult knowledge of the sugar content of sports drinks and whether this knowledge and other characteristics are associated with their sports drink consumption. Design: Nonexperimental. Setting: Nationally representative 2011 Summer ConsumerStyles survey data. Subjects: 3929 U.S. adults. Measures: The outcome variable was sports drink consumption in the past 7 days. The main exposure variable was knowledge about sports drinks containing sugar. The covariates were sociodemographic characteristics, physical activity, and weight status. Analysis: Multivariable logistic regression analysis was used to estimate adjusted odds ratios (ORs) for adults consuming sports drinks ≥1 times/wk after controlling for other characteristics. Results: Approximately 22% of adults reported consuming sports drinks ≥1 times/wk. Most adults (71%) agreed that sports drinks contain sugar; however, this agreement was not significantly associated with adults' sports drink consumption. The odds of drinking sports drinks ≥1 times/wk were significantly higher among younger adults aged 18 to 64 years (OR range: 5.46–2.71), males (OR = 2.09), high-school graduates (OR = 1.52), and highly active adults (OR = 2.09). Conclusion: There were disparities in sports drink consumption by sociodemographic characteristics and physical activity level; however, knowledge of sports drinks' sugar content was not associated with consumption. Understanding why some population groups are higher consumers may assist in the development of education, providing those groups with a better understanding of sports drinks' nutritional value and health consequences of excessive sugar consumption in any form.